Lessons Learned from the Quality of Experience (QoE) Assessment of 4G Mobile Technology in Indonesia - Muhammad Suryanegara; Fery Andriyanto; Ajib Setyo Arifin (Institute of Advanced Engineering and Science, 2018)
The purpose of this research is to assess the quality of experience (QoE) of 4G mobile technology that is used in the Indonesian market. The study analyzed the results obtained and discussed the lesson learned for stakeholders of the telecommunications industry. Primary data was obtained by conducting a market survey in May 2017, with a confidence level of 95%, representing the 4G subscribers in the Indonesia market. There are three main subjective aspects of QoE: service quality, data speed, and network quality (indicated by stability of signal). The analyses were conducted based on ACR-HR score, comparing users’ experiences of 4G with their previous 3G subscriptions. It was found that, in general, the Indonesian market perceived 4G as offering a better experience than 3G. However, one of the important lessons that can be learned is that network operators should provide a more stable signal, as the market gave a lower score for this aspect.